1993
DOI: 10.1039/c39930001157
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide trifluoromethanesulfonates as reusable catalysts: catalytic Friedel-Crafts acylation

Abstract: The Friedel-Crafts acylation of substituted benzenes proceeds smoothly by using a catalytic amount of a lanthanide trifluoromethanesulfonate [Ln(OTf),], which is easily recovered from the reaction mixture and reused without a decrease in catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(65 citation statements)
references
References 7 publications
(2 reference statements)
1
61
0
2
Order By: Relevance
“…In addition, it was found that addition cyclopentadiene in THF/H 2 O (9:1) at room temperature to of lithium perchlorate (LiClO 4 ) as a co-catalyst improved give the corresponding adduct in a 93% yield (endo/exo ϭ the yields dramatically. [21] This novel Sc(OTf) 3 -catalyzed 100:0) (Equation 9). FriedelϪCrafts acylation reaction is remarkable and has advantages over the conventional AlCl 3 -promoted reaction.…”
Section: Friedel-crafts Acylation and Friesmentioning
confidence: 99%
“…In addition, it was found that addition cyclopentadiene in THF/H 2 O (9:1) at room temperature to of lithium perchlorate (LiClO 4 ) as a co-catalyst improved give the corresponding adduct in a 93% yield (endo/exo ϭ the yields dramatically. [21] This novel Sc(OTf) 3 -catalyzed 100:0) (Equation 9). FriedelϪCrafts acylation reaction is remarkable and has advantages over the conventional AlCl 3 -promoted reaction.…”
Section: Friedel-crafts Acylation and Friesmentioning
confidence: 99%
“…[166][167][168][169][170][171][172] Rareearth triflates and especially scandium(III) triflate have been widely explored as Lewis acids to mediate different types of organic reactions, mainly thanks to the pioneering work by Kobayashi. [172][173][174][175][176][177] Major advantages of these rare-earth salts are that they are water-tolerant Lewis acids (in contrast to strong Lewis acids like AlCl 3 ) and that catalytic amounts rather than stoichiometric amounts can be used in many cases. Although the rare-earth salts have to compete in Lewis acid chemistry with other metal salts like indium(III), [178][179][180] gallium(III), 181,182 and bismuth(III) salts, 183-186 they still remain popular reagents for organic synthesis.…”
Section: Lanthanide-mediated Organic Reactionsmentioning
confidence: 99%
“…During the course of our investigations about Friedel-Crafts acylation, we found that acetyl perchlorate, the mixed anhydride of acetic acid and perchloric acid, which acts as an active acylating agent is generated from acetic anhydride and lithium perchlorate in the presence of RE(OTf) 3 . [46][47][48][49] Based on this consideration, the efficient generation of acyl nitrate is expected between an inorganic nitrate and carboxylic anhydride in the presence of RE(OTf) 3 , and we tried to examine the nitration of aromatic compounds using the RE(OTf) 3 -carboxylic anhydride-inorganic nitrate system. …”
mentioning
confidence: 99%
“…In this decade, there have been many reports that RE(OTf) 3 as a Lewis acid catalyst has been successfully applied to several synthetic reactions. [39][40][41][42][43][44][45] Recently, we have developed RE(OTf) 3 catalyzed Friedel-Crafts reactions [46][47][48][49] and benzyl-etherification, 50) and these reactions proceed smoothly using small amounts of RE(OTf) 3 . During the course of our investigations about Friedel-Crafts acylation, we found that acetyl perchlorate, the mixed anhydride of acetic acid and perchloric acid, which acts as an active acylating agent is generated from acetic anhydride and lithium perchlorate in the presence of RE(OTf) 3 .…”
mentioning
confidence: 99%